REDESIGNING THE ROLES OF TUBERCULOSIS TREATMENT SUPPORTER IN INDONESIA - Khoiriningtyas Ayu Puspita; Zeni Yanti; Nuzulul Kusuma Putri; Stefanus Supriyanto; Nurul Atiqah (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: Indonesia is the third-highest rank country for tuberculosis. Many studies already compared the effectiveness of the Directly Observed Treatment-Short (DOTS) course with self-administered therapy (SAT) in tuberculosis treatment and pointed out that DOTS did not improve the succession rate (SR) significantly. The participation of a tuberculosis treatment supporter that has an important rule in the DOTS strategy to improve the patients’ adherence in taking treatment should be reviewed.Aims: The study aims to analyze the determination of environmental factors in the effectiveness of tuberculosis treatment which can lead to the program improvement issue.Method: This research was a cross-sectional study conducted by involving 55 of 121 tuberculosis patients. The sampling frame was tuberculosis patients who were reported under the first and third quarters in Primary Healthcare Center of Tanah Kalikedinding as it had failed to reach the succession rate during 2012-2015.Results: These findings indicated that the social environment of tuberculosis patients significantly contributed to their adherence to taking medicine. It showed that tuberculosis treatment supporters had an essential role in maintaining the patients’ adherence. Tuberculosis treatment supporters who lived in one roof with the patient tended to get 2.265 times risk to be contagious. This study also pointed out that the physical environment had the highest determination in the success rate of treatment.Conclusion: Modifying the physical environment of tuberculosis patients can be the greater alternative program to fight tuberculosis rather than the tuberculosis treatment supporters. Tuberculosis treatment supporters must be provided with universal protection due to their high-risk position to be contagious.Keywords: treatment adherence, DOTS, patient environment, treatment effectiveness.